Numerical simulation of viscous three-dimensional flow over aerospace vehicles using Euler/boundary-layer zonal approach - Amorim, José Carlos C. [UNESP]; Azevedo, João Luiz F. (My University, 1996)
This paper presents a viscous three-dimensional simulations coupling Euler and boundary layer codes for calculating flows over arbitrary surfaces. The governing equations are written in a general non orthogonal coordinate system. The Levy-Lees transformation generalized to three-dimensional flows is utilized. The inviscid properties are obtained from the Euler equations using the Beam and Warming implicit approximate factorization scheme. The resulting equations are discretized and approximated by a two-point fmitedifference numerical scheme. The code developed is validated and applied to the simulation of the flowfield over aerospace vehicle configurations. The results present good correlation with the available data.
Keywords: Aerospace vehicles; Approximation theory; Boundary layers; Calculations; Computer simulation; Equations of motion; Finite difference method; Mathematical transformations; Three dimensional; Euler equation; Factorization method; Levy-Lees transformation; Non orthogonal coordinate system; Viscous flow